Take a proactive approach to negotiating your R&D budget - Brockhoff, Klaus K.
Klaus K. Brockhoff and Alok K. Chakrabarti suggest how R&D executives can compete more effectively against the other business functions for the resources they need.
Are you too defensive? Take advantage of metrics and simulation models to demonstrate R&D's contribution to the firm's strategic performance.
R&D directors continue to behave defensively when negotiating their budgets, while their colleagues who represent other business functions use more aggressive approaches. It is argued that at least four different reasons can explain this behavior : cultural differences between business functions, lack of appropriate data, distance from value creation in the market, and smaller degree of activity standardization. A more offensive approach could be supported by developing R&D metrics that resemble the standard business metrics used in other functional areas. One could also simulate R&D budgeting procedures, the resulting budgets and their consequences.
Keywords: R&D budget